2015
DOI: 10.11646/zootaxa.4020.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Acanthosaura phuketensis (Squamata: Agamidae), a new long-horned tree agamid from southwestern Thailand

Abstract: We describe a new lowland forest-dwelling species of the genus Acanthosaura from Phuket Island and the Phuket mountain range in southwestern Thailand. Acanthosaura phuketensis sp. nov., the 11th species in the genus, seems most closely related to A. crucigera from Myanmar and western Thailand and A. cardamomensis from the Cardamom Mountains, but can be differentiated from them by a combination of morphological and coloration characteristics. This new discovery stresses the importance of preserving t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…Recent studies of the agamid lizard Bronchocela rayanesis showed that species, initially described from Langkawi Island, Malaysia , also occurs on Phuket Island and mainland Phang-nga Province, Thailand (Grismer et al 2016;Zug et al 2017). The tree agamid lizard Acanthosaura phuketensis (Pauwels et al 2015), also seems to occur on both Phuket Island and nearby adjacent Phang-nga, Province. Until sequences from the type locality of T. phuketensis are analyzed, the status of B467 remains problematic.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of the agamid lizard Bronchocela rayanesis showed that species, initially described from Langkawi Island, Malaysia , also occurs on Phuket Island and mainland Phang-nga Province, Thailand (Grismer et al 2016;Zug et al 2017). The tree agamid lizard Acanthosaura phuketensis (Pauwels et al 2015), also seems to occur on both Phuket Island and nearby adjacent Phang-nga, Province. Until sequences from the type locality of T. phuketensis are analyzed, the status of B467 remains problematic.…”
Section: Discussionmentioning
confidence: 99%
“…Paired meristic characters are given as left/right. The list and methodology of measurements and meristic counts follow Wood et al (2010) and Pauwels et al (2015):…”
Section: Methodsmentioning
confidence: 99%
“…NSSPS number of scales surrounding the postorbital spine (in addition to characters abbreviations listed in Pauwelset al 2015);…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative morphological data were taken from original descriptions and subsequent studies (Hardwicke and Gray 1827;Cuvier 1829;Günther 1861Günther , 1864Boulenger 1885Boulenger , 1900Werner 1904;Vogt 1914;Lönnberg 1916;Smith 1935;Taylor 1963;Orlov et al 2006;Ananjeva et al 2008Ananjeva et al , 2011Wood et al 2009Wood et al , 2010Pauwels et al 2015;Nguyen et al 2018;Liu et al 2019;Nguyen et al 2019;Trivalairat et al 2020).…”
Section: Bepmentioning
confidence: 99%